Anti-vibration and traction control of rotary sliding systems by orthogonal rotation providing transverse sliding. (July 2021) - Tadokoro, Chiharu; Aso, Yuto; Nagamine, Takuo; Nakano, Ken
Abstract: Rotary sliding systems such as clutches require smooth motion without any unpredicted vibrations, such as friction-induced vibration. Friction-induced vibration, which is called judder in clutches, sometimes occurs, especially during clutch engagement. To suppress the friction-induced vibration in rotary sliding systems, a unique method in which the direction of the friction force is forcibly changed by orthogonal rotation of a roller providing transverse sliding is proposed. The effectiveness of the method was examined experimentally using a custom-built apparatus. The results show that the orthogonal rotation suppresses the friction-induced vibration even when the friction force exhibits velocity-weakening characteristics. In addition, the effective friction force, which can be regarded as the traction force, can be controlled by varying the orthogonal rotation. Highlights: Orthogonal rotation providing transverse sliding is applied to a rotary sliding system. The orthogonal rotation suppresses friction-induced vibrations in the rotary sliding system. The effect is demonstrated experimentally, and its mechanism is discussed theoretically. The orthogonal rotation also controls the traction force. The effects arise from a change in the direction of frictional force.